HYSTEROSALPINGOGRAPHY AND LAPAROSCOPY IN EVALUATIING FALLOPIAN TUBES IN THE MANAGEMENT OF INFERTILITY IN COTONOU, BENIN REPUBLIC - TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE; OGOUDJOBI, OGOURINDÉ MATHIEU; OBOSSOU, Achille; TAKPARA, ISSIFOU; ALIHONOU, Eusèbe (My University, 2014)
Introduction: Hysterosalpingography, along with laparoscoy, are the most requested examinations for tubal factor exploration for infertility, in developing countries. Object: To compare the results of hysperosalpingography and laparoscopy in patients assessed for infertility. Patients and Method: This was a 5 years retrospective, descriptive study done at the Obstetrics and Gynecology Clinic of the HKM Centre, National University Hospital, Cotonou, Benin Republic. All the patients admitted for infertility of tubal origin were included. These included 96 patients who had undergone hysterosalpingography followed by laparoscopy. The analysis was done with the SPSS version 12.0.1. Results: The mean age of the patients was 33.3 years. Infertility was primary in 66.3% of cases and secondary in 33.7% of cases and the average duration was 48.9 months. Hysterosalpingography diagnosed 9.37% of proximal tubal obstruction while laparoscopy diagnosed same in 17.71%. Besides pelvic adhesive bands seen in 33.33% of cases, laparoscopy was able to visuslize patent tubes with some pathology in 11.46%, and pelvic endometiosis in 6.25% of cases. Conclusion: The results of HSG and those of laparoscopy are complementary in tubal infertility evaluation. While HSG seems to be reliable when the tubes are patent, laparoscopy helps to reveal false tubal obstructions observed with HSG, and also helps in the diagnosis of pelvic adhesive bands and endometriosis.
Keywords: Infertility; Hysterosalpingography; Laparoscopy; Pelvic pathologies